Kitchen Gas Leakage Control System - Abdullah, Nur Fatihah; Abdullah, Nurhanim Saadah (Research and Innovation in Technical and Vocational Education and Training, 2021)
The kitchen gas leakage control system aims to warn users to avoid frequent fires in the kitchen caused by gas leakage. The objective of this study is to design, develop and test the functionality of gas leakage detection systems. The prototype development of this system is based on the Design Thinking model. The LCD display and buzzer can help users to monitor and warn when the gas leaking happens. This gas detector uses the MQ-135 type gas detector to detect the reading value of the gas leak in percentage (%) which is already set in the software. The reading percentage of gas will be shown through the LCD display while the buzzer will make a sound if the gas reading is above 6%. The DC Fan will inhale the leaked gas. In the same time, the solenoid valve will automatically close the hose. The Arduino IDE software is used as the software in this system. The implementation of this project involves testing using gas from a lighter. Expert validation has involved four experts including two lecturers, an electrical technician from the Faculty of Technical and Vocational Education and a technician from Radicare. As a result from the expert evaluation, it shows that the development of the Gas Leakage Control System in the Kitchen has achieved its stated objectives. Therefore, the development of this system is relevant to be developed to assist users in detecting gas leaks.